Optimalisasi Supervisi Pemberian Edukasi Pasien dan Keluarga pada Rumah Sakit di Jakarta Selatan - Pratiwi, Laras Adythia; Yetti, Krisna; Mashudi, Dudi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
The Hospitals are obliged to facilitate patients and families by providing information and education.Education is a supporting factor in participating in the care optimization process. The quality of educationcan be improved by conducting supervision. Supervision is a process of supervising and giving direction bya nursing supervisor to improve the quality of service. This case study aims to optimize the implementationof supervision of patient and family education in hospitals in South Jakarta. Data collected throughobservation, questionnaire distribution and managerial team interviews. An analysis is carried out using afishbone diagram and statistical software. Implementation is carried out by making supervision instrumentsfor providing education and observing document of patient and family education. Results: Theimplementa The Hospitals are obliged to facilitate patients and families by providing information and education.Education is a supporting factor in participating in the care optimization process. The quality of educationcan be improved by conducting supervision. Supervision is a process of supervising and giving direction bya nursing supervisor to improve the quality of service. This case study aims to optimize the implementationof supervision of patient and family education in hospitals in South Jakarta. Data collected throughobservation, questionnaire distribution and managerial team interviews. An analysis is carried out using afishbone diagram and statistical software. Implementation is carried out by making supervision instrumentsfor providing education and observing document of patient and family education. Results: